The Corporate Governance of Privately Controlled Brazilian Firms - Bernard S. Black (Revista Brasileira de Finanças, 2009)
We provide an overview of the corporate governance practices of Brazilian public companies, based primarily on an extensive 2005 survey of 116 companies. We focus on the 88 responding Brazilian private firms which are not majority owned by the state or a foreign company. We identify areas where Brazilian corporate governance is relatively strong and weak. Board independence is an area of weakness: The boards of most Brazilian privatefirms are comprised entirely or almost entirely of insiders or representatives of the controlling family or group. Many firms have zero independent directors. At the same time, minority shareholders have legal rights to representation on the boards of many firms, and this representation is reasonably common. Financial disclosure lags behind world standards. Only a minority of firms provide a statement of cash flows or consolidated financial statements. However, many provide English language financial statements, and an English language version of their website. Audit committees are uncommon, but many Brazilian firms use an alternate approach to ensuring financial statement accuracy - establishing a fiscal board. A minority of firms provide takeout rights to minority shareholders on a sale of control. Controlling shareholders often use shareholders agreements to ensure control.